2005
DOI: 10.4103/0028-3886.16925
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional digital subtraction angiography vs two-dimensional digital subtraction angiography for detection of ruptured intracranial aneurysms: A study of 86 aneurysms

Abstract: 3D-DSA, especially volume-rendering images, tends to depict ruptured intracranial aneurysms bigger than 2D-DSA. This is particularly true with cerebral aneurysms that are < 5 mm in size and are located in the anterior circulation, especially ICA and ACA territories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 11 publications
0
17
0
3
Order By: Relevance
“…b Endoview that shows the proximal (yellow arrow) and distal (blue arrow) radiopaque markers of the nitinol stent and the catheter. uation of intracranial and extracranial arteries [6][7][8][9][10][11][12][13][14][15][16][17][18], together with the usefulness of the technique in planning some types of endovascular treatment such as stent deployment [13][14][15]. Virtual angioscopy is a new modality for imaging the arterial vessels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…b Endoview that shows the proximal (yellow arrow) and distal (blue arrow) radiopaque markers of the nitinol stent and the catheter. uation of intracranial and extracranial arteries [6][7][8][9][10][11][12][13][14][15][16][17][18], together with the usefulness of the technique in planning some types of endovascular treatment such as stent deployment [13][14][15]. Virtual angioscopy is a new modality for imaging the arterial vessels.…”
Section: Discussionmentioning
confidence: 99%
“…Only one paper reported on a preliminary experience with 3DRA [18]. In this study, we have analysed the contribution of virtual angioscopic reconstructions starting from 3DRA and have shown that the quality of these images is satisfactory in a high percentage of ed extracraniche [6][7][8][9][10][11][12][13][14][15][16][17] e il contributo di questa tecnica nella programmazione di alcuni tipi di trattamenti endovascolari cosi come nel posizionamento degli stent [13][14][15].…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Most neurovascular centers also have 3D rotational angiography (3D-DSA). 3D-DSA provides more detailed information in the evaluation of cerebral aneurysms than 2D-DSA [38, 39]. However, in our neurosurgical department, 3D-DSA is not provided as a first-line tool in elderly patients.…”
Section: Discussionmentioning
confidence: 99%